MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI MEDIA KARTU ANGKA DI KELOMPOK A KOBER ASSA’ADAH - Teti Nurhayati; Rohmalina Rohmalina (IKIP Siliwangi, 2020)
The introduction of mathematical concepts is important for children to understand for further education, especially regarding numbers. Because numbers are always used in all activities. Introducing mathematics learning in AUD is done by playing and playing through number card media will be more interesting and children will be enthusiastic about participating in learning. So researchers are interested in researching with the title